ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH (PAD) KABUPATEN MIMIKA - Hengki Derek Wandosa; Arius Kambu; Agustinus Numberi (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2017)
This study aims to determine: (1) The potential revenue (PAD) in Mimika Regency Year 2002-2013; (2) Identify the factors that encourage the growth source revenue (PAD) in Mimika. The method used in analyzing the use of quantitative techniques the 4 quadrant approach to tax (shift and share), elasticity component of revenue (PAD). The results showed that, by classification using the shift and share analysis of the potential components of taxes and levies in Mimika, shows the classification Prima namely Public service levies, and levies Licensing Certain, whereas in the classification Potentially the service levies Enterprises, for the classification of Developing the components Restaurant tax, entertainment tax, advertisement tax, street lighting tax and the classification Retarded Hotel Tax Non Metallic Minerals & Rocks. Based on the calculation of tax elasticity against the regional revenue, obtained information that the sources of growth by component Local Revenue (PAD) that is the average of the component Local Tax gain an Elastic (2.91> 1), Retribution gain an Inelastic (0.22 1). So that through this information, the source of regional revenue growth in Mimika courtesy Realization component Local Tax, Income and Asset enterprises. Keywords : Local Revenue